In-depth characterization of the Wnt-signaling/β-catenin pathway in an in vitro model of Barrett's sequence - Götzel, Katharina; Chemnitzer, Olga; Maurer, Luisa; Dietrich, Arne; Eichfeld, Uwe; Lyros, Orestis; Moulla, Yusef; Niebisch, Stefan; Mehdorn, Matthias; Jansen-Winkeln, Boris; Vieth, Michael; Hoffmeister, Albrecht; et al. (BMC Gastroenterology, 2019)
Background: An altered Wnt-signaling activation has been reported during Barrett's esophagus progression, but with rarely detected mutations in APC and β-catenin (CTNNB1) genes. Methods: In this study, a robust in-depth expression pattern analysis of frizzled receptors, co-receptors, the Wnt-ligands Wnt3a and Wnt5a, the Wnt-signaling downstream targets Axin2, and CyclinD1, as well as the activation of the intracellular signaling kinases Akt and GSK3β was performed in an in vitro cell culture model of Barrett's esophagus. Representing the Barrett's sequence, we used normal esophageal squamous epithelium (EPC-1, EPC-2), metaplasia (CP-A) and dysplasia (CP-B) to esophageal adenocarcinoma (EAC) cell lines (OE33, OE19) and primary specimens of squamous epithelium, metaplasia and EAC. Results: A loss of Wnt3a expression was observed beginning from the metaplastic cell line CP-A towards dysplasia (CP-B) and EAC (OE33 and OE19), confirmed by a lower staining index of WNT3A in Barrett's metaplasia and EAC, than in squamous epithelium specimens. Frizzled 1-10 expression analysis revealed a distinct expression pattern, showing the highest expression for Fzd2, Fzd3, Fzd4, Fzd5, Fzd7, and the co-receptor LRP5/6 in EAC cells, while Fzd3 and Fzd7 were rarely expressed in primary specimens from squamous epithelium. Conclusion: Despite the absence of an in-depth characterization of Wnt-signaling-associated receptors in Barrett's esophagus, by showing variations of the Fzd- and co-receptor profiles, we provide evidence to have a significant role during Barrett's progression and the underlying pathological mechanisms.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Barrett's esophagus; Esophageal adenocarcinoma; Frizzled receptors; Wnt-signaling; Wnt3a